Gut CD103+ dendritic cells express indoleamine 2, 3-dioxygenase which influences T regulatory/T effector cell balance and oral tolerance induction. Issue 5 (28th April 2010) - Matteoli, Gianluca; Mazzini, Elisa; Iliev, Iliyan D; Mileti, Erika; Fallarino, Francesca; Puccetti, Paolo; Chieppa, Marcello; Rescigno, Maria
Abstract : Objective: CD103 + gut dendritic cells (DCs) have been shown to be required for de novo conversion of adaptive T regulatory (Treg) cells. Indoleamine 2, 3-dioxygenase (IDO) is an enzyme involved in tryptophan catabolism that is expressed by DCs isolated from tumour-draining lymph nodes. IDO-expressing DCs sustain and differentiate Tregs. The aim of this study was to investigate the expression and the possible physiological role of IDO in the tolerogenic properties of intestinal DCs. Design: The expression level of IDO in CD103 + and CD103 − DCs was analysed by qRT-PCR, western blot and immunofluorescence. CD103 + and CD103 − DCs were sorted from mesenteric lymph nodes (MLNs) and the small intestinal lamina propria, and the role of IDO in the conversion of Tregs and Th effector cell development was evaluated via specific inhibition or gene deletion. Oral tolerance, experimental colitis and T cell differentiation in vivo were assessed upon IDO inactivation. Results: We show that, primarily, CD103 + but not CD103 − gut DCs express IDO whose inhibition results in reduced CD4 + Foxp3 + T regulatory cell conversion and enhanced T cell proliferation. When IDO was inhibited or genetically deleted there was an increase in Th1 and Th17 differentiation both in vitro and in vivo. Finally, in vivo IDO blockade affected the development of Tregs specific for orally administered antigens, impaired oral tolerance induction and exacerbated colitis. Conclusions: We identified a new IDO-dependent pathway leading to acquisition of tolerogenic functions in mucosal CD103-expressing DCs, indicating IDO as a possible therapeutic target for gut disorders.